De Caro, Mario, “Galileo’s Mathematical Platonism”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 13–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Franchella, Miriam, “L.E.J. Brouwer: Toward Intuitionistic Logic”, Historia Mathematica 22 (1995), 304–322 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Casati, Roberto/Smith, Barry/White, Graham (Hgg.), Philosophy of the Cognitive Sciences. Proceedings of the 16th International Wittgenstein-Symposium, 15–22 August 1993, Kirchberg am Wechsel, Austria, Hölder-Pichler-Tempsky: Wien 1994 (= Schriftenreihe der Wittgenstein-Gesellschaft; 21) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sicherheitserziehung - ein Thema für den Arbeitslehreunterricht. - Bigga, Regine (ARBEIT UND TECHNIK in der Schule)

Visual Modeling and 3D-Representation with a Complete Visual Programming Language --- A Case Study in Manufacturing - Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang; Quintanilla, J.; Tahedl, C.; Weber, A. (Proceedings of the 1996 IEEE Symposium on Visual Languages)
The main goal of the article is to evaluate the suitability of visual programming languages, i.e., Pictorial Janus (K. Kahn and V. Saraswat, 1990), for the modeling of complex systems and their control strategies. These systems can be seen as networks of communicating objects. Objects select strategies for suitable actions based on incoming messages. Our field of investigation is in computer integrated manufacturing considering the example of a car manufacturing cell. This color sorting assembly buffer (CSAB) schedules jobs in queues. The jobs represent car bodies scheduled in feeder lines for the enameling. Feeder lines collect raw bodies to blocks. Blocks are bodies which are to be enameled by the same color. This organization decreases the cost of expensive change-over-times when changing colors at the enamelling. Blocks of bodies are dislocated from the queue and enameled successively. Contradictory system goals, such as minimizing color changes and preserving the sequence of incoming jobs, have to be regarded by appropriate control strategies. Due to the complexity of this (NP complete) problem and to real time requirements for online control there are no optimal strategies on hand. Consequently, suitable heuristics have to be developed. Often they are designed applying a trial-and-error method. A modeling framework has to support the rapid prototyping of these systems as well as an expressive end user oriented representation. Both are essential requirements since end users need other visualization techniques than experienced designers due to their different knowledge and interests.
Keywords: Computer integrated manufacturing; Job shop scheduling; Processor scheduling; Computer languages; Control system synthesis; Computer aided manufacturing; Sorting; Assembly; Costs; Control systems

Computergestützte Intervention bei Rechtschreibschwäche: Effekte eines kognitions- und lernpsychologisch orientierten Trainingsprogramms auf Morphembasis bei sehr schwachen Sonderschülern. - Walther, J.; Bigga, Regine; Bischof, H. (Sonderpädagogik)

Weak Sequential Composition in Process Algebras - Rensink, Arend; Wehrheim, Heike (CONCUR '94, Concurrency Theory, 5th International Conference, Uppsala, Sweden, August 22-25, 1994, Proceedings)

Wozu Algebra der Logik? Ernst Schröders Suche nach einer universalen Theorie der Verknüpfungen - Peckhaus, Volker (Modern Logic)
Abstract: Historia Mathematica 22 (1995), #22.2.62 (I. Anellis). Rezensionen: Zbl. Math. 812.01012 (I. Grattan-Guinness); MR 95m:03002 (M. Guillaume).

Die Gleichstellung der Geschlechter im Lehrplan. Anregungen für Schule und Unterricht. - Bigga, Regine; Braun, F.; Hoffmann, L.

Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld Arbeitslehre - Tornieporth, G.; Bigga, Regine